2002
DOI: 10.1021/jp013355t
|View full text |Cite
|
Sign up to set email alerts
|

14N MAS NMR Spectroscopy and Quadrupole Coupling Data in Characterization of the IV ↔ III Phase Transition in Ammonium Nitrate

Abstract: The first application of 14N MAS NMR spectroscopy and the associated 14N quadrupole coupling data for characterizing a phase transition between two solid phases is presented. For NH4NO3, the transition between the phases IV and III at about 35 °C and the phases themselves are studied by 14N MAS NMR using the NH4 + as well as the NO3 - ion as probes. Spectra are acquired employing spinning speeds in the range from 2000 to 7000 Hz thereby taking advantage of the frictional heating as the heat source. The 14N qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 23 publications
2
39
1
Order By: Relevance
“…Moreover, the value for CH 3 3 C 6 H 5 NI is about an order of magnitude larger than for CH 3 4 NI (C Q D 31.7 kHz). 5 As might be expected, this shows that substitution of a phenyl C 6 H 5 group for a methyl CH 3 group directly onto the ammonium nitrogen has a larger influence on the magnitude of C Q when compared to the effect of substituting the phenyl group for one of the hydrogen (H) atoms in CH 3 Table 1 for the single N-site in CH 3 3 C 6 H 5 NI.…”
Section: (Ch 3 ) 3 (C 6 H 5 )Nisupporting
confidence: 64%
See 1 more Smart Citation
“…Moreover, the value for CH 3 3 C 6 H 5 NI is about an order of magnitude larger than for CH 3 4 NI (C Q D 31.7 kHz). 5 As might be expected, this shows that substitution of a phenyl C 6 H 5 group for a methyl CH 3 group directly onto the ammonium nitrogen has a larger influence on the magnitude of C Q when compared to the effect of substituting the phenyl group for one of the hydrogen (H) atoms in CH 3 Table 1 for the single N-site in CH 3 3 C 6 H 5 NI.…”
Section: (Ch 3 ) 3 (C 6 H 5 )Nisupporting
confidence: 64%
“…5 Only a few cases of NH 4 C salts exhibiting a large number of 14 N MAS sidebands, which allow determination of quite large C Q ( 14 N) values and the associated Á Q parameter, have been published. 3 The present work demonstrates an advancement in the application of solid-state 14 N MAS NMR to the important class and wide range of ammonium salts. 1 H decoupling during acquisition was applied to all spectra recorded for spinning frequencies r Ä 3000 Hz.…”
Section: Introductionmentioning
confidence: 78%
“…1.2 MHz, and Jakobsen and co-workers subsequently published a series of 14 N MAS NMR papers on a range of systems. For example, using the variation in frictional heating of the MAS rotor at various spinning rates, they studied a phase transition in ammonium nitrate (phase IV to III at 35°C) [109]. Both the NH 4 + and NO 3 − ions were observed, and the authors made use of a fully 15 NH 4 + enriched sample to resolve the individual sites, since the sidebands for each species overlap.…”
Section: Broadband Excitationmentioning
confidence: 99%
“…As well as all this, many studies have been performed on AN phase transitions using DSC [21], FTIR [22], XRD [23], Raman spectroscopy [24], NMR [25] and UV-spectroscopy [13]. These have shown that the phase behavior of AN strongly depends on the experimental conditions, such as humidity [26], crystallization method [7], thermal history of sample [7], sample size [27], pressure [28,29], purity of sample [30], sample weight [31].…”
Section: Introductionmentioning
confidence: 99%